2017
DOI: 10.1007/s00264-017-3412-7
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of periprosthetic joint infection using alpha-defensin test or multiplex-PCR: ideal diagnostic test still not found

Abstract: Neither alpha-defensin test nor multiplex-PCR could detect periprosthetic infection immediately and reliably. Multiplex-PCR was suitable for detecting the non-infected but not the truly infected. Alpha-defensin test was helpful but showed no satisfactory results. Conventional microbiological methods remain the most reliable for periprosthetic infection diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
35
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 35 publications
3
35
0
1
Order By: Relevance
“…Our results of clinical samples showed that in periprosthetic tissues PCR has poor sensitivity (15.4% for conventional PCR and 23% for viability PCR) as previously found by Ryu et al [27], Suda et al [28], and Huang et al [29]. They reported sensitivities of 16%, 30.8%, and 34% respectively.…”
Section: Discussionsupporting
confidence: 71%
“…Our results of clinical samples showed that in periprosthetic tissues PCR has poor sensitivity (15.4% for conventional PCR and 23% for viability PCR) as previously found by Ryu et al [27], Suda et al [28], and Huang et al [29]. They reported sensitivities of 16%, 30.8%, and 34% respectively.…”
Section: Discussionsupporting
confidence: 71%
“…Predominantly in low-grade infections, the sensitivity of this biomarker and synovial polymerase chain reaction (PCR), but their diagnostic performance has been found to be inferior to conventional diagnostic methods, with several authors recommending their use as a confirmatory tool in equivocal cases rather than as a screening tool [35,36]. Molecular tests such as synovial PCR did not outperform conventional culture in general, except in infections caused by low-virulent pathogens [37,38]. The clinical value of next generation sequencing (NGS) in the diagnosis of culturenegative PJI is currently investigated.…”
Section: Incomplete Synovial Fluid Analysismentioning
confidence: 99%
“…5 Arthroplasty surgeons have used PCR for the detection of periprosthetic joint infection with mixed results. [6][7][8][9] Positive predictive values were low with a large number of false-positive results in some studies, 6,7,9 but others reported the superior value of PCR for the detection of low virulent bacteria. 8,10 Let us not forget that DNA of bacterial species is also detected in patients with inflammatory knee arthritis, associated degenerative anterior cruciate ligament (ACL) tears, and osteoarthritis.…”
mentioning
confidence: 99%